2012
DOI: 10.24960/jli.v2i1.598.35-41
|View full text |Cite
|
Sign up to set email alerts
|

Pembuatan Biobriket dari Limbah Cangkang Kakao

Abstract: ABSTRAKBiobriket merupakan energi alternatif pengganti bahan bakar yang dihasilkan dari bahan-bahan organik atau limbah pertanian (biomassa) yang kurang termanfaatkan. Beberapa jenis limbah biomassa memiliki potensi yang cukup besar seperti limbah kayu, sekam padi, jerami, ampas tebu, cangkang sawit, dan sampah kota. Potensi lain yang belum tergarap adalah limbah cangkang kakao. Limbah-limbah tersebut apabila tidak dimanfaatkan maka akan menimbulkan bau yang tidak sedap dan dapat merusak ekosistem lingkungan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
6
0
8
Order By: Relevance
“…One of the vegetable waste management processes into an energy resource is bio briquettes production. Biobriquette is an alternative energy substitute for fuel produced from underutilized organic or agricultural waste (biomass) (Martynis, Sundari, and Sari, 2012). In line with the literature on the production of biomass briquettes from a mixture of peanut shells and corncob, charcoal shows that briquettes are effectively used as a renewable alternative fuel source (Purnawarman, Nurchayati, and Padang, 2015) and that there is an increase in cognitive value (N-gain) for students which is marked by an increase in N -gain (Suryani, Farid, and Mayub, 2019).…”
Section: Introductionmentioning
confidence: 88%
“…One of the vegetable waste management processes into an energy resource is bio briquettes production. Biobriquette is an alternative energy substitute for fuel produced from underutilized organic or agricultural waste (biomass) (Martynis, Sundari, and Sari, 2012). In line with the literature on the production of biomass briquettes from a mixture of peanut shells and corncob, charcoal shows that briquettes are effectively used as a renewable alternative fuel source (Purnawarman, Nurchayati, and Padang, 2015) and that there is an increase in cognitive value (N-gain) for students which is marked by an increase in N -gain (Suryani, Farid, and Mayub, 2019).…”
Section: Introductionmentioning
confidence: 88%
“…Figure 9 shows the PDI value at particle size 1000-465 µm and is smaller than the particle size 250 -125, and 105-74 µm. Martynis, Sundari, and Sari (2012) explained that the finer the particle size, the stronger the bio briquette produced. Besides, the size of the two particles indicated that the higher the tapioca content, the higher the PDI value.…”
Section: Percentage Of Durability Index (Pdi)mentioning
confidence: 99%
“…Biobriquettes are briquettes produced from organic materials, agricultural waste, or biomass (Martynis, Sundari, and Sari, 2012). Biobriquette is a coal substitute biofuel that is being developed (Sharman, Priyank, and Sharma, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Peningkatan kebutuhan energi di Indonesia dari tahun ke tahun berdampak pada ketersediaan cadangan energi fosil seperti bahan bakar minyak, gas bumi, dan batu bara yang semakin berkurang [2], sehingga sekarang banyak dilakukan penelitian terkait sumber energi alternatif dalam memenuhi kebutuhan energi di Indonesia [3]. Salah satu energi alternatif yang dikembangkan saat ini adalah briket yang merupakan suatu jenis bahan bakar padat yang berasal dari biomassa maupun limbah bahan organik yang dapat menghasilkan kalor sebesar > 4.000 kal/gr, gas metana, karbon, uap air sebesar < 7,5 %, dan belerang sebesar < 1 % [4]. Sebagai salah satu bentuk bahan bakar baru, briket merupakan bahan yang sederhana, baik dalam proses pembuatan ataupun dari segi bahan baku yang digunakan, sehingga bahan bakar briket memiliki potensi yang cukup besar untuk dikembangkan.…”
Section: Pendahuluanunclassified